Synthesis of Asymmetric Curcumin Analogue (2,6)-2-(3-bromo-4-methoxybenzylidine)-6-(3,4-dimethoxybenzylidine)cyclohexanone with a Base Catalyst - Nafillah, Khoirotun; Ekawati, Linda; Purwanto, Purwanto (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Curcumin analogs are phenolic secondary metabolites that are more stable than curcumin because they do not contain active methylene groups. Generally, these compounds have a symmetric structure, while asymmetric curcumin analogs with higher frequency and potency are rarely synthesized. This study aimed to synthesize asymmetric curcumin analogs from 2-(3,4-dimethoxybenzylidene)cyclohexanone and bromoanisaldehyde. The synthesis was conducted using the Claisen-Schmidt condensation method with a base catalyst in ethanol at 25 °C for 12 hours. The intermediate compound available in the laboratory was characterized using GC-MS, showing a molecular ion (M⁺) at m/z 246. Meanwhile, bromoanisaldehyde was characterized by GC-MS and FT-IR, yielding a molecular ion at m/z 215 and a C–Br stretching vibration peak at 812 cm⁻¹. The study yielded a yellow solid weighing 0.13 g (yield percentage: 2.93%) with a melting point of 143-147 °C. UV-Vis, FT-IR, and HR-MS analysis confirmed the successful synthesis and characterization of the asymmetric curcumin analog, as evidenced by the molecular ion (M⁺) at m/z 443.06274 in the HR-MS spectrum. However, further analysis, such as ¹H-NMR and ¹³C-NMR, is needed to confirm the structure of the compound. Furthermore, research related to bioactivity testing is crucial for obtaining more stable and effective drug candidates.